A sexual and reproductive empowerment framework to explore volitional sex in sub-Saharan Africa. Issue 6 (1st June 2021) - Wood, Shannon N.; Karp, Celia; Tsui, Amy; Kibira, Simon Peter Sebina; Desta, Selamawit; Galadanci, Hadiza; Makumbi, Fredrick; Omoluabi, Elizabeth; Shiferaw, Solomon; Seme, Assefa; Moreau, Caroline
Abstract: Volitional sex is central to the sexual health and well-being of women and girls globally. To date, few studies have examined women's empowerment and its application to sexual health outcomes, including volitional sex. The aim of this study was to explore the relevance of a sexual and reproductive empowerment framework to volitional sex across four geographically and culturally diverse contexts in sub-Saharan Africa. Qualitative data were collected between July and August 2017 in four sites: Ethiopia, Nigeria (Anambra and Kano states) and Uganda. A total of 352 women aged 15–49 and 88 men aged 18 and older were interviewed through 120 in-depth interviews and 38 focus group discussions ( n  = 440 total participants). Results describe the substantial barriers restraining women's sexual choices, particularly norms that stigmatise women's requests for sex, even within marriage. Results further highlight women's internal sexual motivations, particularly related to the enjoyment of sex and the role of sex in strengthening partner relationships. Future empowerment research and measurement should focus not only on sexual constraints, but also integrate internal motivations, in order to fully understand the factors that shape women's sexual health outcomes.